EFEKTIVITAS PENERAPAN UJIAN TANPA PENGAWASAN MELALUI PENDIDIKAN KARAKTER BERBASIS HADIST DI SMA ISLAM ATHIRAH BOARDING SCHOOL BONE - Abdul Hakim; Fajri Dwi Yama (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This study aims to describe the effectiveness of the unsupervised exam program through the character education of students at the Athirah Bone Islamic High School. In this study using descriptive qualitative methods, the subject of the principal's research, curriculum, class teachers, school employees and Athirah Bone Islamic High School students. Data collection techniques using observation, interviews, questionnaires, and documentation. Checking the validity of the data uses triangulation and objectivity. The results showed the effectiveness of the unsupervised exam on character education based on the hadith of Islamic Athirah Bone high school students. Through exams without supervision students have the character of Honesty, discipline, responsibility, independence, and personality.